2019
DOI: 10.12998/wjcc.v7.i12.1430
|View full text |Cite
|
Sign up to set email alerts
|

Non-albicans Candida prosthetic joint infections: a systematic review of treatment

Abstract: BACKGROUND Non- albicans Candida prosthetic joint infections (PJIs) are rare. Optimal treatment involves a two-stage revision surgery in combination with an antifungal agent. However, no clear guidelines have been developed regarding the agent or treatment duration. Hence, a broad range of antifungal and surgical treatments have been reported so far. AIM To clarify treatment of non- albicans Candida PJIs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(50 citation statements)
references
References 50 publications
0
50
0
Order By: Relevance
“…Fungal PJIs are a relatively infrequent [ 7 , 8 ], albeit potentially devastating, complication of joint replacement surgery [ 9 ] reported to account for just 1.45–3.1% of all confirmed infections involving primary TKAs or THAs [ [10] , [11] , [12] ]. The rate has been proposed to be higher in the re-revision setting.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Fungal PJIs are a relatively infrequent [ 7 , 8 ], albeit potentially devastating, complication of joint replacement surgery [ 9 ] reported to account for just 1.45–3.1% of all confirmed infections involving primary TKAs or THAs [ [10] , [11] , [12] ]. The rate has been proposed to be higher in the re-revision setting.…”
Section: Discussionmentioning
confidence: 99%
“…The rate has been proposed to be higher in the re-revision setting. Previous investigations have suggested that Candida albicans represents the most commonly encountered periprosthetic fungal infection of the knee (80–88% of cases) [ 8 , [13] , [14] , [15] ], with non-Candida species PJIs considered relatively rare [ 9 ]. While “classic” descriptions have inferred an underlying immunocompromised host requirement, recent review of the literature did not support this in most cases [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We present a previously unreported case of fungal PJI with the organism C. parapsilosis following a TEA. Most PJIs, including those involving the shoulder, hip and knee, are caused by the organisms Staphylococcus aureus and S epidermidis , whereas fungal organisms represent a mere 1% of the etiologies, with the Candida species being the most common [1, 3, 510]. The decision to perform an initial surgical debridement, bushing exchange, and implant retention was based on the well-fixed implants, minimal patient symptoms, and the concern for bone loss in the setting of elbow explantation [11].…”
Section: Discussionmentioning
confidence: 99%